OPTIMIZING GAS STATION LOCATION USING GENETIC ALGORITHMS - Handayanto, Rahmadya Trias; Soenyoto, Soedarmin; Handoyo, Yopi (Universitas Islam 45 Bekasi, 2013)
Gas station location is not only based on financial but also environment aspects because it will give negative impact if there are some accidents such as fire, tank leakage, etc. Helping customer in supplying fuels should not sacrifice other needs such as health, food, education, living circumstance, and so on. Therefore we propose the system that can help someone deciding and analyzing the location of gas station, especially when doing proper analysis. By using genetic algorithms our system can find optimum location of gas station after considering other important location that must be far away from it. The distance from important place was counted by normal euclidean after converting road and the river at map into nonlinear equation using interpolation. Population was generated from converting road on the map into equation. The important places that must be far away from gas station are collected and with that equation then give an objective function. Testing result showed the system could find optimum gas stations location at Bekasi regency. Keywords : GAS STATION, GENETIC, ALGORITHMS